THE THE EFFECTIVITY OF GIVING PROGRESSIVE MUSCLE RELAXATION COMPARED TO AROMATHERAPY MASSAGE TO IMPROVE SLEEPING QUALITY OF WOMEN EMPLOYEES IN BALI ROYAL HOSPITAL DENPASAR - Diahputri, Ni Made Nuari; Narta Dewi, Anak Ayu Nyoman Trisna; Handari Adiputra, Luh Made Indah Sri (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 2 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i02.p01, 2018)
ABSTRACT          Sleeping quality is someone’s satisfaction about his or her sleeping to rest their body and mind in order to reduce fatigue. The Progressive Muscle Relaxation (PMR) and Aromatherapy Massage are some of the therapy relaxation used to improve the sleeping quality. The Wilcoxon Sign Rank Test showed significant results with p value=0,007 (p<0,05) in Progressive Muscle Relaxation (PMR) group and p value=0,006 (p<0,05) in Aromatherapy Massage group, that means there was significance difference of the increase of sleeping quality before and after intervention. The result of Mann-Whitney U-test revealed there was no difference on mean of sleeping quality score improvement between Progressive Muscle Relaxation (PMR) and Aromatherapy Massage group, with p value=0.738 (p>0.05). It can be concluded that Progressive Muscle Relaxation (PMR) is as good as Aromatherapy Massage in improving sleeping quality of women employees in Bali Royal Hospital Denpasar. Keyword : Sleeping quality, Progressive Muscle Relaxation, Aromatherapy Massage, Pittsburgh Sleep Quality Index Questioner.